The global strong solutions of the 3D incompressible Hall-MHD system with variable density - An, Shu; Chen, Jing; Han, Bin (Mathematical Modelling and Analysis, 2024)
In this paper, we focus on the well-posedness problem of the three-dimensional incompressible viscous and resistive Hall-magnetohydrodynamics system (Hall-MHD) with variable density. We mainly prove the existence and uniqueness issues of the density-dependent incompressible Hall-magnetohydrodynamic system in critical spaces on .